Efecto de metformina sobre las vías de señalización asociadas al desarrollo y la progresión del cáncer colorrectal - Amable, Gastón Federico (2020)
Currently, there is an increase in the incidence and prevalence of obesity and metabolic syndrome, pathologies that drive to complex disease like cardiovascular illness, type 2 diabetes mellitus (T2DM) and oncology disease such as colorectal cancer (CRC).\nThe CRC is of one the most common type of cancer and the second cause of death by cancer in Argentina. Unfortunately, there is no effective treatment for this disorder except for surgery in early stages together or not with chemotherapy.\nRecently, epidemiological evidence suggests that metformin, the most frequently prescribed anti-diabetic agent, shows activities as preventive agent of different types of cancer including the CRC. Nevertheless, the mechanisms by which metformin exerts these therapeutics effects is still unknown.\nOur results show that metformin inhibits ?-catenin Ser552 phosphorylation through PI3K/Akt pathway inhibition in an AMPK-dependent manner. Metformin promotes ?-catenin/E-cadherin/p-120-catenin plasmatic membrane translocation, focal adhesion kinase and motility inhibition interfering with central pathways associated to CRC development and progression.